2010
DOI: 10.1534/genetics.110.119115
|View full text |Cite
|
Sign up to set email alerts
|

BUD22 Affects Ty1 Retrotransposition and Ribosome Biogenesis in Saccharomyces cerevisiae

Abstract: A variety of cellular factors affect the movement of the retrovirus-like transposon Ty1. To identify genes involved in Ty1 virus-like particle (VLP) function, the level of the major capsid protein (Gag-p45) and its proteolytic precursor (Gag-p49p) was monitored in a subset of Ty1 cofactor mutants. Twenty-nine of 87 mutants contained alterations in the level of Gag; however, only bud22D showed a striking defect in Gag processing. BUD22 affected the 11 translational frameshifting event required to express the Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 64 publications
(97 reference statements)
6
82
1
Order By: Relevance
“…In S. cerevisiae, a 4.9-kb Ty1i RNA is detected in wild- type strains both in our work and in previous studies when poly (A) ϩ RNA is subjected to Northern blotting (22,54) but is rarely detected in numerous studies when total RNA is analyzed (7,8,18,(58)(59)(60). Perhaps, the level of RNA degradation observed with the abundant 5.7-kb Ty1 genomic RNA obscures the 4.9-kb Ty1i transcript when total RNA is analyzed by Northern blotting, because we can detect a shorter Ty1i transcript produced from a pGPOL⌬ plasmid with total RNA from S. paradoxus.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In S. cerevisiae, a 4.9-kb Ty1i RNA is detected in wild- type strains both in our work and in previous studies when poly (A) ϩ RNA is subjected to Northern blotting (22,54) but is rarely detected in numerous studies when total RNA is analyzed (7,8,18,(58)(59)(60). Perhaps, the level of RNA degradation observed with the abundant 5.7-kb Ty1 genomic RNA obscures the 4.9-kb Ty1i transcript when total RNA is analyzed by Northern blotting, because we can detect a shorter Ty1i transcript produced from a pGPOL⌬ plasmid with total RNA from S. paradoxus.…”
Section: Discussionsupporting
confidence: 70%
“…Final PCR products were subcloned into pGPOL⌬ using BstXI and BglII restriction sites. Plasmid pBDG1534 was generated from plasmid pBDG606 (pGTy1his3-AI/Cen-URA3) (18) by replacing the URA3 marker for TRP1. Briefly, TRP1 was amplified from BY4742 with primers containing flanking URA3 sequence (20718uratrpfwd, 5=-ATGTCGAAAGCTACATATAAGGAACGTGCTGCTA CTCATCAATTCGGTCGAAAAAAGAAA-3=; 20916uratrprev, 5=-AGCTTTT TCTTTCCAATTTTTTTTTTTTCGTCATTATAATATGCTTGCTTTTCA AAAGGC-3=), and the PCR product was cotransformed into yeast with pBDG606 linearized within URA3 with ApaI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…H2AZ replaces H2A in nucleosomes, and it is the region of nucleosomal DNA near the H2A/H2B interface that was most highly targeted by Ty1. Further, S. cerevisiae strains lacking H2AZ show decreased levels of Ty1 transposition (Dakshinamurthy et al 2010), and decreases in levels of H2A and H2B alter patterns of integration at the CAN1 locus (Rinckel and Garfinkel 1996). To evaluate more specifically a role for H2AZ in targeting, we performed logistic regression using models that test whether H2AZ is preferentially associated with hot or cold class III gene targets (data not shown).…”
Section: Ty1 Targets Nucleosomesmentioning
confidence: 99%
“…Disruption of the chromatin structure upstream of tRNA genes disrupts the periodicity of Ty1 element insertion but not integration site selection (15,16). Although many nuclear factors have been identified that either restrict or promote Ty1 integration, proteins that physically interact with Ty1-IN to target it upstream of Pol III-transcribed genes have remained elusive until recently (17)(18)(19)(20)(21)(22). Ty1-IN interacts with separase, a protein that cleaves the cohesin complex to mediate separation of sister chromatids (23).…”
mentioning
confidence: 99%